Effects of Ergo-Cycle Exercise on Lung Function and Physical Fitness of Chronic Obstructive Pulmonary Disease - Lister Napitupulu; Sri Wahyudati (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives : To observe the effect of ergo-cycle exercise on lung functional capacity and physical fitness level of COPD patients, to observe relationship between lung functional capacity and physical fitness level of COPD patients before and after regular ergo-cycle exercise.Methods : Quasi-experimental research of twenty eight subjects with mild and moderate COPD who came to Medical Rehabilitation Instalation. They conducted ergo-cycle exercise for 30 minutes 3 times a week, by one day interval, for 4 weeks. This research was a pre and post test design.Results :There was significant increase on some lung function parameters such as % FEV1, % FVC, but it didn’t happen with FEV1/FVC ratio (p<0.001; p<0.001; p = 0.3). The result of measurement 6-MWD indicated a significant increase score (p<0.001).There was a significant change on severity of COPD before and after ergo-cycle exercise for 4 weeks. Mild COPD as 8 subjects at the initial study became 15 subjects after the exercise, and moderate COPD as 20 subjects became 13 subjects after the exercise (p=0.002). Relationship of lung functional capacity with 6-MWD indicated significant correlation on % FEV1 and % FVC, but not on % FEV1/ %FVC ratio.Conclusions : Thirty minutes ergo-cycle exercise for 3 times a week within 4 weeks is respectively able to increase lung functional capacity and physical fitness level of mild and moderate COPD patients. There is positive correlation between lung functional capacity with physical fitness level on COPD patients.Keywords: COPD; Lung Functional Capacity; Physical Fitness Level; Ergo-static Bicycle Exercise;6-MWT.